Úlceras por pressão em pessoas com câncer recebendo cuidados paliativos domiciliares - Queiroz, Ana Carolina de Castro Mendonça (2013)
Patients with advanced cancer are impaired in their various dimensions and therefore have a higher risk for developing pressure ulcers (PU). Little is known about the magnitude of this problem in patients receiving palliative care which hampers progress in comprehensive care for the patient and family. In order to broaden the understanding of the topic, this study was developed with the purpose to analyze the pressure ulcers and the risk for development of pressure ulcers in cancer patients receiving palliative home care. This is a longitudinal, descriptive and quantitative approach, closed cohort, conducted at the Grupo de Apoio Paliativo ao Paciente Oncológico of the Associação de Combate ao Câncer de Goiás, from December 2011 to July 2012. Data collection was performed on 7 evaluations. The first evaluation was undertaken at the patient’s home through interview and clinical assessment of patients. The remaining evaluations were done via telephone 7, 14, 21 and 28 days after the first evaluation. Forty-five and 90 days after the date of inclusion in the study, patients were assessed for survival. Data on sociodemographic, clinical, PU (when present), risk of PU by the Braden Scale and if patient was alive or not was collected. Descriptive analysis was performed as well as the Fisher exact test and associations were considered significant when p<0.05. The study included 64 patients with cancer in palliative care (68.8% male, 45.3% white, 54.7% under 70 years old, 62.5% with KPS <50%, 57.8% with urinary incontinence). Forty-six patients completed the evaluations to D28, and at 45 and 90 days, a total of 25 and 33 participants had died, respectively. Twelve (18.8%) patients had PU. Of these, 75.0% were men, they had one to three PUs, totaling 19 lesions, of which 89.4% started at home and 47.4% were stage 3 lesions. The only statistically significant difference between the groups was that the presence of PU was more frequent among those who already had a history of previous wound. There was an increased risk of PU throughout the study period and found that the risk for PU was higher in those who died within 45 days after the first evaluation. There was no significant association between PU and survival using the Kaplan-Meier method (p=0.072). PU consisted of a significant event occurring in the population studied and the risk increased with the approach of death. This indicates that systematic care for prevention of PU to reduce risk and achieve early diagnosis of PU should be performed by palliative care health team, minimizing the suffering of terminal patients.